Specific covalent binding of platelet-derived growth factor to human plasma alpha 2-macroglobulin. - Huang, J S (1984)
Attempts to measure the platelet-derived growth factor (PDGF) in human plasma resulted in the discovery of a specific plasma binding protein. The 125I-labeled PDGF (125I-PDGF)-plasma binding protein complex retained mitogenic activity but lost reactivity against rabbit anti-PDGF antiserum. Copurification of the plasma binding protein and alpha 2-macroglobulin (alpha 2M) in human plasma, the formation of a complex between 125I-PDGF and purified alpha 2M, and the comigration of the 125I-PDGF-plasma binding protein complex and the 125I-PDGF-alpha 2M complex in NaDodSO4/polyacrylamide gel electrophoresis and in pore-limiting polyacrylamide gel electrophoresis strongly suggested that alpha 2M is the plasma binding protein for 125I-PDGF. Immunoprecipitation of 125I-PDGF-alpha 2M and 125I-PDGF-plasma binding protein complexes by anti-human alpha 2M antiserum further established that alpha 2M and the plasma binding protein are the same molecule. Approximately 20% of 125I-PDGF is complexed by alpha 2M; further 125I-PDGF is complexed if the remaining 125I-PDGF is incubated with additional alpha 2M. Complex formation of 125I-PDGF with plasma or with alpha 2M was completely inhibited by 0.2 mM p-chloromercuric benzoate or 0.2 mM N-ethylmaleimide. The 125I-PDGF-alpha 2M complex or 125I-PDGF-plasma binding protein complex was not dissociated by 8 M urea, 1 M acetic acid, 0.1 M NaOH, or 1% NaDodSO4 but was dissociated by 2-mercaptoethanol, suggesting that the covalent binding of 125I-PDGF to alpha 2M occurs through a disulfide/sulfhydryl exchange reaction. The 125I-PDGF-alpha 2M complex (780,000 daltons) appears to contain two molecules of 125I-PDGF and two dimers of alpha 2M. The precise physiological role of the 125I-PDGF-alpha 2M interaction is unknown. alpha 2M may serve to limit PDGF released locally at sites of blood vessel injury. Alternatively, because of the nearly complete homology between the partial amino acid sequence of PDGF and the predicted amino acid sequence of the transforming protein of the simian sarcoma virus, p28sis, alpha 2M may play an important role in limiting the activity of a PDGF-like activity expressed by virus-transformed cells.